2013
DOI: 10.1111/1556-4029.12192
|View full text |Cite
|
Sign up to set email alerts
|

Stature Estimation from Foramen Magnum Region in Chinese Population

Abstract: Estimation of stature from body parts plays a vital role in identifying the dead. This study focused on dimensions of the foramen magnum region and examined the relationship between stature and the dimensions of the foramen magnum region in northern and southern Chinese populations. Measurements were taken on the skulls of 276 individuals (all male). Data on 48 individuals from northern China and 140 from southern China were used for further stature reconstruction of the above two populations in China. Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 17 publications
(23 reference statements)
0
8
2
8
Order By: Relevance
“…Measurements were used for stature reconstruction and statistical analyses indicated that bilateral variation is insignificant for all measurements except maximum length of condyle in the southern Chinese population with a p value less than 0.01 and that the northern and southern populations differ significantly only in the minimum distance between condyles. Linear and multiple regression equations for stature estimation were established in this study [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were used for stature reconstruction and statistical analyses indicated that bilateral variation is insignificant for all measurements except maximum length of condyle in the southern Chinese population with a p value less than 0.01 and that the northern and southern populations differ significantly only in the minimum distance between condyles. Linear and multiple regression equations for stature estimation were established in this study [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cadaveric length was measured in the supine position between the vertex of the head and the heel with a steel measuring tape to the nearest 0.1 cm [20,24]. To this a correction factor of 2.5 cm was applied as illustrated by Trotter and Gleser as a measure of living standing height [24].…”
Section: Methodsmentioning
confidence: 99%
“…Długość zwłok mierzono w pozycji leżącej, między wierzchołkiem głowy a piętą, za pomocą stalowej taśmy mierniczej z dokładnością do 0,1 cm [20,24]. W tym celu zastosowano współczynnik korekcji 2,5 cm, za Trotter i Gleser, jako miary wzrostu żywej osoby w pozycji stojącej [24].…”
Section: Metodologiaunclassified
See 2 more Smart Citations